Oxytocin ameliorates lipopolysaccharide-induced acute orchitis model: interplay of oxidative stress and inflammatory pathways - El-Sherbiny, Mohamed; Elkattawy, Hany A.; Hadhoud, Shimaa; Nasr, Ahmed N.; Ibrahim, Ateya M.; Ameer, Omar Z.; Alsaleebi, Noorhan; Asfari, Joud; Zakari, Madaniah O.; Mojaddidi, Moaz A.; Ali, Ehab K.; Almohaimeed, Hailah M.; et al. (Frontiers in Pharmacology, 2025)
IntroductionLipopolysaccharide (LPS), a constituent of the outer membrane of Gram-negative bacteria, is a powerful inducer of systemic inflammation and has been extensively utilized in experimental models to simulate inflammatory responses and septic disorders. Recent research indicates that oxytocin (OXY), a neuropeptide typically linked to social bonding and reproductive functions, may influence inflammatory processes. This work examines the impact of OXY on LPS-induced testicular damage, aiming to elucidate its therapeutic potential in addressing inflammatory disorders and broadening the comprehension of its functions beyond conventional neuroendocrine roles.MethodsEighteen male albino rats were divided into three groups; the control group received no treatment; the LPS group received 0.5 mL of saline solution containing 5 mg/kg LPS intraperitoneally (orchitis model); and the LPS + OXY group received LPS and OXY (0.1 mg/kg) intraperitoneally every 12 h for 72 h.Results and discussionAnimals subjected to LPS were found to have severe orchitis, as evidenced by increased oxidative stress and surging inflammatory mediators (TNF-α, IL-1β, and IL-6), with declined IL-10 levels. Besides, LPS increased the malondialdehyde (MDA) and decreased the glutathione (GSH) levels, inducing an oxidative stress cascade. In addition, there are dramatic increases in the TLR4, MyD88, NF-κB, and PK2/PKR1 protein expression levels. All these events could alter the sperm count, morphology, and testicular architecture.ConclusionInterestingly, OXY could mitigate LPS-induced oxidative damage and inflammation in testicular tissue alongside restoring the disrupted sperm count, motility, and morphology. This therapeutic potential of OXY might be accounted for by its anti-inflammatory, antioxidant, and antiapoptotic activities.